Ethical Leadership and Its Role in Organizational Commitment - Hafizullah Hakimi (Business Ethics and Leadership, 2025)

(untitled)
Ethical leadership fosters organizational commitment, particularly within public institutions such as the Ministry of Finance. This study delves into the role of ethical leadership on organizational commitment within the context of the Ministry of Finance. In addition, the research also strives to assess employee commitment and pinpoint the factors that might lead to ethical leadership and stronger commitment. To attain the stated goals, the study included a sample of 344 employees applied at the Ministry of Finance of Afghanistan as a public institution in February 2025, selected via the Cochran sampling method. This study employed quantitative, survey-based descriptive research design, utilizing a structured questionnaire for data collection. The questionnaire was designed to assess employees’ perceptions of ethical leadership and its impact on their organizational commitment within the Ministry of Finance. The data were analyzed using SPSS software, where Pearson’s correlation coefficient and regression analysis were applied to examine the relationships between variables. Descriptive statistics like variance, mean, median, and mode were also used to describe the results. The research and data analysis findings, by revealing a significant positive correlation between ethical leadership and organizational commitment, prove that ethical leadership plays a crucial role in the organizational commitment of the public sector. Specifically, the correlation coefficient of 0.814 indicates a strong direct relationship. A more detailed examination of the individual components reveals that elements of ethical leadership have the most pronounced effect on employee organizational commitment. The findings illustrate the pivotal role of ethical leadership in fostering both organizational commitment and overall organizational outcomes. These findings hold the potential to guide administrators and policymakers in improvising strategies aimed at elevating employee commitment, satisfaction, motivation, retention, and output, thereby playing a pivotal role in supporting performance and operational efficiency.